Pemberdayaan Teknologi Informasi untuk Keunggulan Bisnis - Supriyanto, - (Jurnal Ekonomi dan Pendidikan, 2012)
Nowadays, IT maintenance is mostly needed by the companies, even small scale companies. It must be supported by 4 (four) factors to be a key in increasing competition power and competitive advantages for the companies. They are (1) IT management system; (2) IT storage management; (3) IT defense system and (4) Pervasive management. By the way, companies which won’t maintenance the four factors will be a looser in the business competition. That’s way IT maintenance is a must for every companies to reach their competitive advantages.